Analysis of efficiency and factors affecting the production of cabbage farming (Brassica oleracea L.) in Belung village, Poncokusumo, Malang, Indonesia (International Journal of Agricultural Research, Innovation and Technology, 2016)
The purpose of this research was to analyze the efficiency and the factors that affect the production of cabbage farm in the village of Belung, Poncokusumo, Malang, Indonesia. Samples taken by census the number of respondents 36 farmers. The analysis used is descriptive qualitative and quantitative. Quantitative analysis include analysis of costs, revenues, income, efficiency and Cobb-Douglas. Based on the analysis, known that farmer acceptance is Rp. 43,767,361 and generated revenues of Rp. 30,124,372/ ha. Result relevated that the Cabbage farm in the village of Belung, Poncokusumo, Malang was highly efficient and profitable with an efficiency of 3.2. Factors that effect significantly on cabbage farming production are labors, lands, pesticides and seeds. Input combinations are already efficient and optimal pesticides and seeds.Int. J. Agril. Res. Innov. & Tech. 6 (1): 8-13, June, 2016